Carbon-metal composite film and preparation method and application thereof

By growing and etching the metal film in a high-temperature furnace, and reacting with aniline and APS in the acidic solution, the carbon-metal composite film is prepared, which solves the problems of high production cost, low efficiency and insufficient electromagnetic shielding performance in the prior art, and achieves efficient and low-cost electromagnetic shielding performance improvement.

CN119530752APending Publication Date: 2025-02-28JIANGSU FEYNMAN SEMICON TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411669496.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In the prior art, the preparation cost of carbon-metal composite films is relatively high, the efficiency is not high, and the electromagnetic shielding performance needs to be further improved.

Method used

The carbon-metal composite film was prepared by heating and growing in a high-temperature furnace with a mixed atmosphere of inert gas and hydrogen, followed by etching under a nitrogen atmosphere and reacting with aniline and APS in an acidic solution.

Benefits of technology

It realizes low-cost and high-efficiency carbon-metal composite film preparation, improves electromagnetic shielding performance, meets different application needs, and extends the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530752A_ABST
    Figure CN119530752A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon-metal composite film and a preparation method and application thereof, belongs to the technical field of carbon nanomaterials, and is used for solving the problems that in the prior art, a carbon-metal composite film is high in preparation cost and low in efficiency, and electromagnetic shielding performance needs to be further improved. The preparation method of the carbon-metal composite film comprises the following steps: preparing a metal film I by adopting a chemical vapor deposition method; etching to obtain a metal film II; adding the metal film II into an acidic solution, adding aniline and APS, and reacting to obtain a carbon-metal composite film; according to the preparation method provided by the invention, the cost is reduced, the efficiency is higher, and the prepared carbon-metal composite film not only improves the stability, but also has good electrical measurement shielding performance, and is more suitable for the field of electronics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of carbon nanomaterials, and in particular to a carbon-metal composite film and a preparation method and application thereof. Background Art

[0002] Nanomaterials can be divided into nanofilms, nanofibers, nanomultilayers and nanoblocks according to their macroscopic structures; they can be divided into nanorods and nanotubes according to their spatial forms, two-dimensional nano-thin films, multilayers and three-dimensional nanoblocks. The preparation methods of nanomaterials can be divided into gas phase method, liquid phase method and solid phase method according to the state of raw materials. Among them, the gas phase method includes gas phase evaporation method, chemical vapor deposition method and chemical vapor condensation method. Among them, the nanomaterials obtained by chemical vapor deposition method have the advantages of high purity, small particle size, good dispersibility and high chemical reaction activity. Compared with the liquid phase method, it is better to prepare metal and carbide ultrafine particles that are difficult to prepare.

[0003] Nanoparticles of metallic iron, nickel and their alloys have many applications in the fields of electronics, optoelectronics, etc., and their electromagnetic shielding plays an important role. Electromagnetic shielding refers to the use of various materials and technologies to block or reduce the propagation and interference of electromagnetic waves to protect electronic equipment and systems from electromagnetic interference (EMI) and electromagnetic radiation (EMR). This field is of great significance in many industries such as communications, consumer electronics, military, and medical. Metal nanoparticles are particularly sensitive to temperature, light, magnetic field, etc. in their environment due to their special volume and surface effects, and their stability needs special attention. For this reason, people modify the surface of metallic iron and nickel nanoparticles, including surfactant modification, coupling agent modification, surface grafting modification, etc., but these modification methods all show a certain degree of timeliness and are not long-lasting. At the same time, due to the high specific surface area of ​​metal nanoparticles, a thin surface oxide film will also cause oxidation of part of the volume, resulting in a decrease in the total activity of metal nanoparticles per unit volume or unit mass, thereby hindering the full play of the unique properties of metal nanoparticles. At present, people can coat metal nanoparticles by arc discharge, but this method has byproducts, low purity, low efficiency, and the equipment used for preparation is complex, energy-intensive, and costly, which is not conducive to large-scale synthesis, limiting its use to a certain extent. Therefore, people need a more stable, low-cost, and efficient treatment method for metal particles to expand the scope of application and make it show more stable performance.

[0004] Chinese patent CN103921520A discloses a carbon nanotube film composite material, in which a functional material is deposited on a carbon nanotube film as a bottom layer, one or more carbon nanotube films are stacked thereon by a binder as an intermediate layer, and a layer of carbon nanotube film containing the functional material deposited is stacked on the intermediate layer by a binder. The prepared carbon nanotube film composite material has certain electrical conductivity, thermal conductivity and magnetic conductivity; however, due to the effect of the binder between the layers, the electrical conductivity, thermal conductivity and magnetic conductivity will be reduced, and the more layers there are, the greater the impact. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a carbon-metal composite film and its preparation method and application, which solves the problems in the prior art that the preparation cost of carbon-metal composite films is high, the efficiency is low and the electromagnetic shielding performance needs to be further improved.

[0006] In order to achieve the above object, the present invention provides a method for preparing a carbon-metal composite film, comprising the following steps:

[0007] Step (1) placing the cleaned metal film in the middle of a quartz boat, pushing it to the center of the left temperature zone of the integrated dual-temperature zone high-temperature furnace, introducing an inert gas to discharge the remaining oxygen or water vapor in the quartz tube; introducing a mixed atmosphere of inert gas and hydrogen and maintaining it for a period of time; introducing a C source gas, and heating and growing in the integrated dual-temperature zone high-temperature furnace until the growth is completed; stopping introducing the C source gas, cooling, and removing the quartz boat to obtain a metal film I;

[0008] Step (2) placing the metal film I with its front side facing upward on the liquid surface of the etching solution for etching, washing the remaining film after etching, and drying it with nitrogen to obtain the metal film II;

[0009] Step (3) Under a nitrogen atmosphere, add the metal film II to the acidic solution, add aniline and APS, stir, react, and after the reaction is completed, filter, wash, and dry to obtain a carbon-metal composite film.

[0010] Preferably, in step (1), the metal in the metal film is Fe or Ni.

[0011] Preferably, in step (1), the thickness of the metal film is 20-500 μm and the purity is 99.995%.

[0012] Preferably, in step (1), the inert gas is argon.

[0013] Preferably, in step (1), a mixed atmosphere of inert gas and hydrogen is introduced and maintained for a period of time, specifically: a mixed atmosphere of 60-90 sccm of high-purity hydrogen and 150-250 sccm of high-purity argon is introduced for 10-15 minutes.

[0014] Preferably, in step (1), the substance used for cleaning the metal film is any one of anhydrous ethanol and acetone.

[0015] Preferably, in step (1), the specific conditions for heating growth in the integrated dual-temperature zone high-temperature furnace are: heating from room temperature to 400-450°C at a heating rate of 15-25°C / min and maintaining for 15-30 minutes for preheating; heating from the preheating temperature to 950-1050°C at a heating rate of 15-25°C / min and growing for 10-20 minutes.

[0016] Preferably, in step (1), the C source gas is methane with a purity of 5%.

[0017] Preferably, in step (2), the washing material is an aqueous solution of n-butanol, wherein the volume ratio of n-butanol to water is 1:(600-1200).

[0018] Preferably, in step (2), the etching solution is a mixture of ammonium thiosulfate, n-butanol and water, wherein the usage ratio of ammonium thiosulfate, n-butanol and water is (0.8-1g):(2-12ml):(200-1200ml).

[0019] Preferably, in step (3), the mass ratio of metal film II, acidic solution, aniline and APS is (60-80):(2000-4000):(200-400):(140-260); the reaction temperature is 6-10°C, and the reaction time is 12-16h.

[0020] Preferably, the carbon-metal composite film is prepared by the method for preparing the carbon-metal composite film.

[0021] Preferably, the thickness of the carbon layer in the carbon-metal composite film is 0.4 nm-11 μm.

[0022] Preferably, the carbon in the carbon-metal composite film is graphene or graphite.

[0023] Preferably, the carbon-metal composite film is used in electromagnetic shielding.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The present invention provides a method for preparing a carbon-metal composite film, which has low cost, simple process flow, is conducive to large-scale production, and has good safety. In the present invention, the electromagnetic shielding performance of the carbon-metal composite film can be flexibly adjusted by adjusting the thickness of the carbon layer, the type and size of the metal film, to meet different application requirements and increase the scope of application. The carbon-metal composite film prepared by the present invention has good electrical, magnetic and thermal conductivity, especially in the field of electronics.

[0026] 2. In the present invention, metallic iron and nickel have good magnetism and can effectively absorb and shield the magnetic field components in electromagnetic waves. Their high magnetic permeability makes the electromagnetic waves in the magnetic field part decay rapidly inside them, thereby enhancing the electromagnetic shielding effect of the composite material; at the same time, the magnetism of metallic iron and nickel is usually stronger than that of their oxides, and they can more effectively shield the magnetic field. The smaller the scale structure in the metal film, the more effectively these properties can be enhanced. Under the action of the initiator APS, the carbon layer and aniline in the metal film II undergo an in-situ polymerization reaction to obtain a carbon-metal composite film; polyaniline has a certain conductivity, and its addition can increase the conductivity, which is beneficial to the electromagnetic shielding performance; the active sites on its surface promote the growth of graphene and graphite; at the same time, it further prevents oxidation or corrosion of the metal part and prolongs the service life of the material.

[0027] 3. In the present invention, the metal film, carbon layer and polyaniline in the carbon-metal composite film can jointly provide the effect of electromagnetic shielding. The metal film absorbs the magnetic field and electric field components through its magnetism and conductivity, while the carbon layer enhances its absorption capacity of electromagnetic waves through its high specific surface area and electronic properties. The conductive polyaniline further increases the conductivity on the surface of the carbon layer, thereby making the carbon-metal composite film play a more comprehensive role in electromagnetic shielding. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a bar graph of the electromagnetic shielding performance test of Example 1 and Comparative Examples 1-2 in the present invention. DETAILED DESCRIPTION

[0029] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Example 1

[0031] This embodiment provides a method for preparing a carbon-metal composite film, comprising the following steps:

[0032] Step (1) Place a metal Fe film with a thickness of 20 μm and a purity of 99.995% after cleaning with acetone in the middle of a quartz boat, push it to the center of the left temperature zone of an integrated dual-temperature zone high-temperature furnace, introduce 150 sccm of high-purity argon for 5 minutes, and discharge the remaining oxygen or water vapor in the quartz tube; introduce a mixed atmosphere of 60 sccm of high-purity hydrogen and 150 sccm of high-purity argon for 10 minutes; introduce 5% pure methane, set an integrated dual-temperature zone high-temperature furnace for heating and growth, and complete the growth; stop introducing methane, cool to room temperature, remove the quartz boat, and obtain metal film I;

[0033] The specific conditions for heating growth in the integrated dual-temperature zone high-temperature furnace are: preheating from room temperature to 400°C at a heating rate of 15°C / min and maintaining for 30 minutes; heating from the preheating temperature to 950°C at a heating rate of 15°C / min and growing for 20 minutes;

[0034] Step (2) placing the metal film I with its front side facing upward on the surface of an etching solution composed of ammonium thiosulfate, n-butanol and water in a ratio of 0.8 g:2 ml:200 ml, etching at 20° C. for 80 min, and washing the remaining film with an aqueous solution of n-butanol and drying with nitrogen to obtain a metal film II;

[0035] Wherein, the volume ratio of n-butanol to water in the n-butanol aqueous solution is 1:600;

[0036] Step (3) under a nitrogen atmosphere, adding the metal film II to a 1 mol / L hydrochloric acid aqueous solution, adding aniline and APS, stirring at a speed of 140 r / min for 6 min, at a temperature of 6° C. for 16 h, after the reaction is completed, filtering, washing with distilled water, and drying at a temperature of 60° C. for 6 h to obtain a carbon-metal composite film with a carbon layer thickness of 0.78 nm;

[0037] Among them, the carbon layer is graphene;

[0038] Wherein, the mass ratio of metal film II, hydrochloric acid aqueous solution, aniline and APS is 60:2000:200:140.

[0039] Example 2

[0040] This embodiment provides a method for preparing a carbon-metal composite film, comprising the following steps:

[0041] Step (1) Place a metal Fe film with a thickness of 20 μm and a purity of 99.995% after cleaning with acetone in the middle of a quartz boat, push it to the center of the left temperature zone of an integrated dual-temperature zone high-temperature furnace, introduce 200 sccm of high-purity argon for 7 minutes, and discharge the remaining oxygen or water vapor in the quartz tube; introduce a mixed atmosphere of 75 sccm of high-purity hydrogen and 200 sccm of high-purity argon for 13 minutes; introduce 5% pure methane, set an integrated dual-temperature zone high-temperature furnace for heating and growth, and complete the growth; stop introducing methane, cool to room temperature, remove the quartz boat, and obtain metal film I;

[0042] The specific conditions for heating growth in the integrated dual-temperature zone high-temperature furnace are: preheating from room temperature to 425°C at a heating rate of 20°C / min and maintaining for 22 minutes; heating from the preheating temperature to 1000°C at a heating rate of 20°C / min and growing for 15 minutes;

[0043] Step (2) placing the metal film I with its front side facing upward on the surface of an etching solution composed of ammonium thiosulfate, n-butanol and water in a dosage ratio of 0.8 g:2 ml:200 ml, etching at 22° C. for 60 min, and washing the remaining film with an aqueous solution of n-butanol and drying with nitrogen to obtain a metal film II;

[0044] Wherein, the volume ratio of n-butanol to water in the n-butanol aqueous solution is 1:800;

[0045] Step (3) under a nitrogen atmosphere, adding the metal film II to a 1.5 mol / L hydrochloric acid aqueous solution, adding aniline and APS, stirring at a speed of 170 r / min for 5 min, at a temperature of 8° C. for 14 h, after the reaction is completed, filtering, washing with distilled water, and drying at a temperature of 70° C. for 5 h to obtain a carbon-metal composite film with a carbon layer thickness of 6 μm;

[0046] Wherein, the carbon layer is graphene;

[0047] Wherein, the mass ratio of metal film II, hydrochloric acid aqueous solution, aniline and APS is 70:3000:300:200.

[0048] Example 3

[0049] This embodiment provides a method for preparing a carbon-metal composite film, comprising the following steps:

[0050] Step (1) Place a metal Fe film with a thickness of 20 μm and a purity of 99.995% after cleaning with acetone in the middle of a quartz boat, push it to the center of the left temperature zone of an integrated dual-temperature zone high-temperature furnace, introduce 250 sccm of high-purity argon for 10 minutes, and discharge the remaining oxygen or water vapor in the quartz tube; introduce a mixed atmosphere of 90 sccm of high-purity hydrogen and 250 sccm of high-purity argon for 15 minutes; introduce 5% pure methane, set an integrated dual-temperature zone high-temperature furnace for heating and growth, and complete the growth; stop introducing methane, cool to room temperature, remove the quartz boat, and obtain metal film I;

[0051] The specific conditions for heating growth in the integrated dual-temperature zone high-temperature furnace are: preheating from room temperature to 450°C at a heating rate of 25°C / min and maintaining for 15 minutes; heating from the preheating temperature to 1050°C at a heating rate of 25°C / min and growing for 10 minutes;

[0052] Step (2) placing the metal film I with its front side facing upward on the surface of an etching solution composed of ammonium thiosulfate, n-butanol and water in a ratio of 0.8 g:2 ml:200 ml, etching at 25° C. for 40 min, and washing the remaining film with an aqueous solution of n-butanol and drying with nitrogen to obtain a metal film II;

[0053] Wherein, the volume ratio of n-butanol to water in the n-butanol aqueous solution is 1:600;

[0054] Step (3) under a nitrogen atmosphere, adding the metal film II to a 2 mol / L hydrochloric acid aqueous solution, adding aniline and APS, stirring at a speed of 200 r / min for 4 min, at a temperature of 10° C. for 12 h, after the reaction is completed, filtering, washing with distilled water, and drying at a temperature of 80° C. for 4 h to obtain a carbon-metal composite film with a carbon layer thickness of 11 μm;

[0055] Among them, the carbon layer is graphene;

[0056] Wherein, the mass ratio of metal film II, hydrochloric acid aqueous solution, aniline and APS is 80:4000:400:260.

[0057] Example 4

[0058] This embodiment provides a method for preparing a carbon-metal composite film, comprising the following steps:

[0059] Step (1) Place a metal Ni film with a thickness of 20 μm and a purity of 99.995% after cleaning with acetone in the middle of a quartz boat, push it to the center of the left temperature zone of an integrated dual-temperature zone high-temperature furnace, introduce 150 sccm of high-purity argon for 5 minutes, and discharge the remaining oxygen or water vapor in the quartz tube; introduce a mixed atmosphere of 60 sccm of high-purity hydrogen and 150 sccm of high-purity argon for 10 minutes; introduce 5% pure methane, set an integrated dual-temperature zone high-temperature furnace for heating and growth, and complete the growth; stop introducing methane, cool to room temperature, remove the quartz boat, and obtain metal film I;

[0060] The specific conditions for heating growth in the integrated dual-temperature zone high-temperature furnace are: preheating from room temperature to 400°C at a heating rate of 15°C / min and maintaining for 30 minutes; heating from the preheating temperature to 950°C at a heating rate of 15°C / min and growing for 20 minutes;

[0061] Step (2) placing the metal film I with its front side facing upward on the surface of an etching solution composed of ammonium thiosulfate, n-butanol and water in a ratio of 0.8 g:2 ml:200 ml, etching at 20° C. for 80 min, and washing the remaining film with an aqueous solution of n-butanol and drying with nitrogen to obtain a metal film II;

[0062] Wherein, the volume ratio of n-butanol to water in the n-butanol aqueous solution is 1:600;

[0063] Step (3) under a nitrogen atmosphere, adding the metal film II to a 1 mol / L hydrochloric acid aqueous solution, adding aniline and APS, stirring at a speed of 140 r / min for 6 min, at a temperature of 6° C. for 16 h, after the reaction is completed, filtering, washing with distilled water, and drying at a temperature of 60° C. for 6 h to obtain a carbon-metal composite film with a carbon layer thickness of 0.52 nm;

[0064] Among them, the carbon layer is graphene;

[0065] Wherein, the mass ratio of metal film II, hydrochloric acid aqueous solution, aniline and APS is 60:2000:200:140.

[0066] Example 5

[0067] This embodiment provides a method for preparing a carbon-metal composite film, comprising the following steps:

[0068] Step (1) Place a metal Ni film with a thickness of 20 μm and a purity of 99.995% after cleaning with acetone in the middle of a quartz boat, push it to the center of the left temperature zone of an integrated dual-temperature zone high-temperature furnace, introduce 200 sccm of high-purity argon for 7 minutes, and discharge the remaining oxygen or water vapor in the quartz tube; introduce a mixed atmosphere of 75 sccm of high-purity hydrogen and 200 sccm of high-purity argon for 13 minutes; introduce 5% pure methane, set an integrated dual-temperature zone high-temperature furnace for heating and growth, and complete the growth; stop introducing methane, cool to room temperature, remove the quartz boat, and obtain metal film I;

[0069] The specific conditions for heating growth in the integrated dual-temperature zone high-temperature furnace are: preheating from room temperature to 425°C at a heating rate of 20°C / min and maintaining for 22 minutes; heating from the preheating temperature to 1000°C at a heating rate of 20°C / min and growing for 15 minutes;

[0070] Step (2) placing the metal film I with its front side facing upward on the surface of an etching solution composed of ammonium thiosulfate, n-butanol and water in a dosage ratio of 0.8 g:2 ml:200 ml, etching at 22° C. for 60 min, and washing the remaining film with an aqueous solution of n-butanol and drying with nitrogen to obtain a metal film II;

[0071] Wherein, the volume ratio of n-butanol to water in the n-butanol aqueous solution is 1:800;

[0072] Step (3) under a nitrogen atmosphere, adding the metal film II to a 1.5 mol / L hydrochloric acid aqueous solution, adding aniline and APS, stirring at a speed of 170 r / min for 5 min, at a temperature of 8° C. for 14 h, after the reaction is completed, filtering, washing with distilled water, and drying at a temperature of 70° C. for 5 h to obtain a carbon-metal composite film with a carbon layer thickness of 5.4 μm;

[0073] Among them, the carbon layer is graphene;

[0074] Wherein, the mass ratio of metal film II, hydrochloric acid aqueous solution, aniline and APS is 70:3000:300:200.

[0075] Example 6

[0076] This embodiment provides a method for preparing a carbon-metal composite film, comprising the following steps:

[0077] Step (1) Place a metal Ni film with a thickness of 20 μm and a purity of 99.995% after cleaning with acetone in the middle of a quartz boat, push it to the center of the left temperature zone of an integrated dual-temperature zone high-temperature furnace, introduce 250 sccm of high-purity argon for 10 minutes, and discharge the remaining oxygen or water vapor in the quartz tube; introduce a mixed atmosphere of 90 sccm of high-purity hydrogen and 250 sccm of high-purity argon for 15 minutes; introduce 5% pure methane, set an integrated dual-temperature zone high-temperature furnace for heating and growth, and complete the growth; stop introducing methane, cool to room temperature, remove the quartz boat, and obtain metal film I;

[0078] The specific conditions for heating growth in the integrated dual-temperature zone high-temperature furnace are: preheating from room temperature to 450°C at a heating rate of 25°C / min and maintaining for 15 minutes; heating from the preheating temperature to 1050°C at a heating rate of 25°C / min and growing for 10 minutes;

[0079] Step (2) placing the metal film I with its front side facing upward on the surface of an etching solution composed of ammonium thiosulfate, n-butanol and water in a ratio of 0.8 g:2 ml:200 ml, etching at 25° C. for 40 min, and washing the remaining film with an aqueous solution of n-butanol and drying with nitrogen to obtain a metal film II;

[0080] Wherein, the volume ratio of n-butanol to water in the n-butanol aqueous solution is 1:600;

[0081] Step (3) under a nitrogen atmosphere, adding the metal film II to a 2 mol / L hydrochloric acid aqueous solution, adding aniline and APS, stirring at a speed of 200 r / min for 4 min, at a temperature of 10° C. for 12 h, after the reaction is completed, filtering, washing with distilled water, and drying at a temperature of 80° C. for 4 h to obtain a carbon-metal composite film with a carbon layer thickness of 9.3 μm;

[0082] Wherein, the carbon layer is graphene;

[0083] Wherein, the mass ratio of metal film II, hydrochloric acid aqueous solution, aniline and APS is 80:4000:400:260.

[0084] Example 7

[0085] This embodiment provides a method for preparing a carbon-metal composite film, comprising the following steps:

[0086] Step (1) Place a metal Fe film with a thickness of 20 μm and a purity of 99.995% after cleaning with acetone in the middle of a quartz boat, push it to the center of the left temperature zone of an integrated dual-temperature zone high-temperature furnace, introduce 150 sccm of high-purity argon for 5 minutes, and discharge the remaining oxygen or water vapor in the quartz tube; introduce a mixed atmosphere of 60 sccm of high-purity hydrogen and 150 sccm of high-purity argon for 10 minutes; introduce 5% pure methane, set an integrated dual-temperature zone high-temperature furnace for heating and growth, and complete the growth; stop introducing methane, cool to room temperature, remove the quartz boat, and obtain metal film I;

[0087] The specific conditions for heating growth in the integrated dual-temperature zone high-temperature furnace are: preheating from room temperature to 400°C at a heating rate of 15°C / min and maintaining for 30 minutes; heating from the preheating temperature to 1000°C at a heating rate of 15°C / min and growing for 10 minutes;

[0088] Step (2) placing the metal film I with its front side facing upward on the surface of an etching solution composed of ammonium thiosulfate, n-butanol and water in a ratio of 0.8 g:2 ml:200 ml, etching at 20° C. for 80 min, and washing the remaining film with an aqueous solution of n-butanol and drying with nitrogen to obtain a metal film II;

[0089] Wherein, the volume ratio of n-butanol to water in the n-butanol aqueous solution is 1:600;

[0090] Step (3) under a nitrogen atmosphere, adding the metal film II to a 1 mol / L hydrochloric acid aqueous solution, adding aniline and APS, stirring at a speed of 140 r / min for 6 min, at a temperature of 6° C. for 16 h, after the reaction is completed, filtering, washing with distilled water, and drying at a temperature of 60° C. for 6 h to obtain a carbon-metal composite film with a carbon layer thickness of 0.55 nm;

[0091] Among them, the carbon layer is graphite;

[0092] Wherein, the mass ratio of metal film II, hydrochloric acid aqueous solution, aniline and APS is 60:2000:200:140.

[0093] Example 8

[0094] This embodiment provides a method for preparing a carbon-metal composite film, comprising the following steps:

[0095] Step (1) Place a metal Ni film with a thickness of 20 μm and a purity of 99.995% after cleaning with acetone in the middle of a quartz boat, push it to the center of the left temperature zone of an integrated dual-temperature zone high-temperature furnace, introduce 150 sccm of high-purity argon for 5 minutes, and discharge the remaining oxygen or water vapor in the quartz tube; introduce a mixed atmosphere of 60 sccm of high-purity hydrogen and 150 sccm of high-purity argon for 10 minutes; introduce 5% pure methane, set an integrated dual-temperature zone high-temperature furnace for heating and growth, and complete the growth; stop introducing methane, cool to room temperature, remove the quartz boat, and obtain metal film I;

[0096] The specific conditions for heating growth in the integrated dual-temperature zone high-temperature furnace are: preheating from room temperature to 400°C at a heating rate of 15°C / min and maintaining for 30 minutes; heating from the preheating temperature to 1000°C at a heating rate of 15°C / min and growing for 10 minutes;

[0097] Step (2) placing the metal film I with its front side facing upward on the surface of an etching solution composed of ammonium thiosulfate, n-butanol and water in a ratio of 0.8 g:2 ml:200 ml, etching at 20° C. for 80 min, and washing the remaining film with an aqueous solution of n-butanol and drying with nitrogen to obtain a metal film II;

[0098] Wherein, the volume ratio of n-butanol to water in the n-butanol aqueous solution is 1:600;

[0099] Step (3) under a nitrogen atmosphere, adding the metal film II to a 1 mol / L hydrochloric acid aqueous solution, adding aniline and APS, stirring at a speed of 140 r / min for 6 min, at a temperature of 6° C. for 16 h, after the reaction is completed, filtering, washing with distilled water, and drying at a temperature of 60° C. for 6 h to obtain a carbon-metal composite film with a carbon layer thickness of 0.4 nm;

[0100] Among them, the carbon layer is graphite;

[0101] Wherein, the mass ratio of metal film II, hydrochloric acid aqueous solution, aniline and APS is 60:2000:200:140.

[0102] Comparative Example 1

[0103] This comparative example provides a method for preparing a carbon-metal composite film, comprising the following steps:

[0104] Step (1) Place a metal Fe3O4 film with a thickness of 20 μm and a purity of 99.995% after cleaning with acetone in the middle of a quartz boat, push it to the center of the left temperature zone of an integrated dual-temperature zone high-temperature furnace, introduce 150 sccm of high-purity argon for 5 minutes, and discharge the remaining oxygen or water vapor in the quartz tube; introduce a mixed atmosphere of 60 sccm of high-purity hydrogen and 150 sccm of high-purity argon for 10 minutes; introduce 5% pure methane, set an integrated dual-temperature zone high-temperature furnace for heating and growth, and complete the growth; stop introducing methane, cool to room temperature, remove the quartz boat, and obtain metal film I;

[0105] The specific conditions for heating growth in the integrated dual-temperature zone high-temperature furnace are: preheating from room temperature to 400°C at a heating rate of 15°C / min and maintaining for 30 minutes; heating from the preheating temperature to 950°C at a heating rate of 15°C / min and growing for 20 minutes;

[0106] Step (2) placing the metal film I with its front side facing upward on the surface of an etching solution composed of ammonium thiosulfate, n-butanol and water in a ratio of 0.8 g:2 ml:200 ml, etching at 20° C. for 80 min, and washing the remaining film with an aqueous solution of n-butanol and drying with nitrogen to obtain a metal film II;

[0107] Wherein, the volume ratio of n-butanol to water in the n-butanol aqueous solution is 1:600;

[0108] Step (3) under a nitrogen atmosphere, adding the metal film II to a 1 mol / L hydrochloric acid aqueous solution, adding aniline and APS, stirring at a speed of 140 r / min for 6 min, at a temperature of 6° C. for 16 h, after the reaction is completed, filtering, washing with distilled water, and drying at a temperature of 60° C. for 6 h to obtain a carbon-metal composite film with a carbon layer thickness of 0.32 nm;

[0109] Among them, the carbon layer is graphene;

[0110] Wherein, the mass ratio of metal film II, hydrochloric acid aqueous solution, aniline and APS is 60:2000:200:140.

[0111] Comparative Example 2

[0112] This comparative example provides a method for preparing a carbon-metal composite film, comprising the following steps:

[0113] Step (1) Place a metal Fe3O4 film with a thickness of 20 μm and a purity of 99.995% after cleaning with acetone in the middle of a quartz boat, push it to the center of the left temperature zone of an integrated dual-temperature zone high-temperature furnace, introduce 150 sccm of high-purity argon for 5 minutes, and discharge the remaining oxygen or water vapor in the quartz tube; introduce a mixed atmosphere of 60 sccm of high-purity hydrogen and 150 sccm of high-purity argon for 10 minutes; introduce 5% pure methane, set an integrated dual-temperature zone high-temperature furnace for heating and growth, and complete the growth; stop introducing methane, cool to room temperature, remove the quartz boat, and obtain metal film I;

[0114] The specific conditions for heating growth in the integrated dual-temperature zone high-temperature furnace are: preheating from room temperature to 400°C at a heating rate of 15°C / min and maintaining for 30 minutes; heating from the preheating temperature to 950°C at a heating rate of 15°C / min and growing for 20 minutes;

[0115] Step (2) placing the metal film I with its front side facing upward on the surface of an etching solution composed of ammonium thiosulfate, n-butanol and water in a dosage ratio of 0.8 g:2 ml:200 ml, etching at 20° C. for 80 min, and washing the remaining film with an aqueous solution of n-butanol and drying with nitrogen to obtain a carbon-metal composite film with a carbon layer thickness of 0.25 nm;

[0116] Among them, the carbon layer is graphene.

[0117] The electromagnetic shielding performance of the carbon-metal composite film prepared in Example 1 and Comparative Examples 1-2 was tested, and a vector network analyzer was used in conjunction with a waveguide measurement system, wherein the test frequency band of the waveguide measurement system covered the X band (8-12.4 GHz) and the Ku band (12.4-18 GHz), and the two ports of the waveguide measurement system were connected to the corresponding ports of the vector network analyzer, and the signal was transmitted from the vector network analyzer to the waveguide measurement system and acted on the carbon-metal composite film. Each test was performed three times until the test results tended to be uniform, and the middle value was taken and recorded. The specific results are shown in Table 1:

[0118] Table 1

[0119]

[0120] It can be seen from the test results in Table 1 that the carbon-metal composite film in Example 1 shows a good electromagnetic shielding value. Graphene is a material with extremely high electrical conductivity, good electron mobility, and can effectively conduct current, enhance the absorption and shielding ability of electromagnetic waves. The thicker the carbon layer, the more electron channels it can provide, enhance its electrical properties, and have a higher electrical conductivity, which helps to improve the electromagnetic shielding effect; in the metal Fe3O4 film, Fe3O4 is a ferromagnetic material, but its magnetic permeability is lower than that of iron, and it is not as good as pure iron when shielding the magnetic field. It can be seen that the electromagnetic shielding performance of Example 1 is worse than that of Comparative Example 1. Under the action of the initiator APS, the metal film II and aniline undergo an in-situ polymerization reaction to obtain a carbon-metal composite film, in which the polyaniline has a certain conductivity, which can compensate for the electrical performance loss caused by the electrically insulating magnetic particles. Once it is missing, its electrical performance naturally decreases. Compared with Comparative Example 1, Comparative Example 2 lacks the conductive polyaniline, and its electromagnetic shielding performance is naturally lower than that of Comparative Example 1.

[0121] Although the embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that all equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A method for preparing a carbon-metal composite film, characterized in that: The following steps are involved: Step (1) placing the cleaned metal film in the middle of a quartz boat, pushing it to the center of the left temperature zone of the integrated dual-temperature zone high-temperature furnace, introducing an inert gas to discharge the remaining oxygen or water vapor in the quartz tube; introducing a mixed atmosphere composed of an inert gas and hydrogen and maintaining it for a period of time; introducing a C source gas, and heating and growing in the integrated dual-temperature zone high-temperature furnace until the growth is completed; stopping introducing the C source gas, cooling, and removing the quartz boat to obtain a metal film I; Step (2) placing the metal film I with its front side facing upward on the liquid surface of the etching solution for etching, washing the remaining film after etching, and drying it with nitrogen to obtain the metal film II; Step (3) Under a nitrogen atmosphere, add the metal film II to the acidic solution, add aniline and APS, stir, react, and after the reaction is completed, filter, wash, and dry to obtain a carbon-metal composite film.

2. The method for preparing a carbon-metal composite film according to claim 1, characterized in that: In step (1), the metal in the metal film is Fe or Ni.

3. The method for preparing a carbon-metal composite film according to claim 1, characterized in that: In step (1), the material used for cleaning the metal film is any one of anhydrous ethanol and acetone.

4. The method for preparing a carbon-metal composite film according to claim 1, characterized in that: In step (1), the specific conditions for heating growth in the integrated dual-temperature zone high-temperature furnace are: heating from room temperature to 400-450°C at a heating rate of 15-25°C / min and maintaining for 15-30 minutes for preheating; heating from the preheating temperature to 950-1050°C at a heating rate of 15-25°C / min and growing for 10-20 minutes.

5. The method for preparing a carbon-metal composite film according to claim 1, characterized in that: In step (1), the C source gas is methane with a purity of 5%.

6. The method for preparing a carbon-metal composite film according to claim 1, characterized in that: In step (2), the washing material is an aqueous solution of n-butanol, wherein the volume ratio of n-butanol to water is 1:(600-1200).

7. The method for preparing a carbon-metal composite film according to claim 1, characterized in that: In step (2), the etching solution is a mixture of ammonium thiosulfate, n-butanol and water, wherein the usage ratio of ammonium thiosulfate, n-butanol and water is (0.8-1g):(2-12ml):(200-1200ml).

8. The method for preparing a carbon-metal composite film according to claim 1, characterized in that: In step (3), the mass ratio of metal film II, acidic solution, aniline and APS is (60-80):(2000-4000):(200-400):(140-260); the reaction temperature is 6-10°C, and the reaction time is 12-16h.

9. A carbon-metal composite film prepared by the method for preparing a carbon-metal composite film according to any one of claims 1 to 8.

10. Use of the carbon-metal composite film according to claim 9 in electromagnetic shielding.

Citation Information

Patent Citations

  • Carbon nano tube film composite material and preparation method thereof

    CN103921520A